Duas novas especies de Veturius Kaup, 1871 (Coleoptera: Passalidae) da Amazonia Brasileira - Vasconcelos Da Fonseca, Claudio Ruy (Instituto de Ecología, A.C., 1999)
Two new species of Veturius from the Armazón basin are described and illustrated.